Abordagem CTS e IHC: A importância das cores no design de interfaces de software - Marcante Lati Cerutti, Diolete; Szesz Junior, Albino (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4207, 2018)
This article describes a teaching experience by using STS (Science, Technology and Society) approach in the HCI (Human-Computer Interaction). The experience was carried out in classes about the use of colors in interface design. It aimed at observing students´ perceptions about the use of STS approach in HCI and its impacts on the course of Project of Information Systems. The methodology used in the experiment was to organize the content (colors and STS) within a didactic sequence of six classes. In this sequence, class themes, pedagogical strategies, aims and content were defined. Results showed more interaction between students and lecture in HCI and more students’ interest on using an appropriated code of colors in interface design in the course of Project of Information Systems. It was concluded that engaging methodologies such as STS approach are important and can impact positively for teaching-learning process of students in Software Engineering.